Pengendalian Persediaan Bahan Baku Sarung Tenun Dengan Pendekatan Economic Order Quantity Kecamatan Cerme Gresik - Yadi Rizky Rahman; Budiyono Pristyadi (Universitas Muhammadiyah Gresik, 2022)
Raw material inventory is an important factor in supporting the company's production activities. Raw material purchase scheduling can increase productivity. When the company is faced with continuous demand, supplies control should be done optimally. This research aims to carry out the control of raw materials method of Economic Order Quantity in the casing of weaving in the Jenggolok hamlet, Gedangkulut Village Cerme-Gresik subdistrict. This type of research is qualitative research. By using the Economic Order Quantity approach, the ordering of optimal raw materials, Reorder Point, and Safety stock can be found. Based on the results of the study indicate that the purchase of raw materials using the Economic Order Quantity method is more optimal than the raw material inventory method used in the previous Jenggolok hamlet. This research can be taken into consideration by the weaving sarong business in applying the EOQ method to determine the optimal order quantity of raw materials and can reduce inventory costs incurred. This research is only done on controlling the supply of raw materials of weaving holster business in Jenggolok Hamlet cerme-gresik sub-district.